DIFFERENCES INCREASING ABILITY OF MATHEMATICAL AND VISUAL THINKING APPROACH BETWEEN BRAIN BASED APPROACH LEARNING WITH EXPOSITORY ON STUDENTS IN MTs PRIVATE MEDAN INTEREST RATE - Elsida Aritonang (Universitas Negeri Makassar, 2018)
Brain Based Learning is a concept to create learning that is oriented towards attempting to optimize student’s brain potential. This study aimed at examine (1) Are there any differences in mathematical reasoning skills of students which are taught by Brain Based Learning approach and expository; (2) Are there any differences in the acquirement of students who are taught by Visual Thinking Brain Based Learning approach and Expository; (3) What steps to resolve the student’s answers related reasoning skills in each lesson; (4) What steps to resolve the student’s answers related to visual thinking abilities in each lesson. This study is a quasi-experiment research. The population of this study is all students of class VIII MTs Bunga Bangsa Medan. The first class experiment is given approach treatment of Brain Based Learning and the second class experiment is given expository approach treatment. In this research has been already developed several learning tools such as lesson plans and student activity sheets. The instruments are used to collect data in this study are: (1) the test of reasoning mathematic ability, (2) the test of visual thinking ability, (3) the steps of student’s answers related to reasoning ability, and (4) the steps of student’s answers related to visual thinking ability. The test is used a form of description that has been declared valid and reliable by the reliability coefficient of 0,84 and 0,86. Regression equations in the class of Brain-Based Learning approach is YBBL = 35,47 + 0,75XBBL and in the Expository approach class is YEks = 24,68 + 0,83XEks. Analysis inferential data is done by analysis of covariance (ANACOVA). The results showed that: (1) The ability of the student’s in mathematic reasoning application of Brain Based Learning approach is higher than expository approach. This is evident from the results ANACOVA for Fhitung = 8.3309 is greater than Ftable = 3.993. (2) The ability of student’s in mahtematic visual thinking in application of of Brain Based Learning approach is higher than expository approach. This is evident from the results ANACOVA for Fhitung = 6.7759 is greater than Ftable = 3.993. (3) the step of completion reasoning test is obtained who has answered correctly for Brain Based Learning class is more than the expository class and (4) the step of completion visual thinking test is obtained who has answered correctly for Brain Based Learning class is more than the expository class